PERTIMBANGAN HAKIM DALAM PUTUSAN KASUS ASURANSI SYARIAH - Linggar Ekapaksi; A.M Hasan Ali (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
This study aims to determine and analyze the judge's considerations in the case of sharia insurance cases in the Religious Courts in Decision Number 426/Pdt.G/2021/PA.JS as well as knowing what factors encourage a judge in deciding sharia insurance cases.This study uses a qualitative method using a normative juridical approach. The source of data used in this study is primary data in the form of a copy of Decision Number 426/Pdt.G/2021/PA.JS obtained from the Directory of Decisions of the Supreme Court of the Republic of Indonesia. Secondary data in this study is in the form of data that supports the explanation of primary data. The results of this study indicate that the judge did not bring the sharia insurance agent in front of the trial, even though the plaintiff repeatedly mentioned the name of the sharia insurance agent. So from the root of the problem, according to the author, the judge's considerations are very rigid, and in the judge's consideration, stating that the company is legal and the company is not in default is questionable. However, in the judge's decision, which is of the opinion that the insurance participant's premium money is returned totally very wise.